Storage of Methane in Resin Carbon Beads and Discs - Emmanuelle Alain; Brian McEnaney (Adsorption Science & Technology)
Porous resin beads can be produced by the emulsion polycondensation of lignosulphonates with crosslinking agents. These resins can be converted into active carbon beads or pressed into discs that can be converted into active carbon monoliths. The stored methane volumetric capacity of the active carbon discs exceeded 150 v/v while the delivered capacity approached this value. The delivered capacity could be increased if steps were taken to release the large amount of methane retained in micropores after decompression. The volumetric methane capacities of the carbon beads were lower than those for the discs due to the presence of interparticulate voids.